The Effectiveness Of The Death Penalty In Indonesia Through A Human Rights Perspective (A Comparative Study Of The Application Of The Death Penalty With Australia) - Nadia Marsya Ramdhani; Khoirunnisa Putri Diksy; Daniella Sitanggang; Kirana Amelia (Journal of Ius Comparatum Law Studies, 2025)
The death penalty is included in the main punishment and is currently regulated in Law No. 1 of 2023 or the new Criminal Code as an alternative punishment and last resort. One of the death penalty cases occurred in 2015 against Andrew Chan and Myuran Sukumaran, two of the nine Bali Nine drug syndicates from Australia. However, Australia rejected the execution because there are differences in the application of the death penalty which Australia has abolished the death penalty. The purpose of this study is to find out how the comparison of the application of the death penalty in Indonesia with Australia and how the effectiveness of the death penalty in Indonesia through a human rights perspective. Through the normative research method with a legislative approach and a comparative approach by comparing with Australia, it can be seen that there are differences in the application of the death penalty in Indonesia and Australia where Australia has abolished the death penalty as a form of protecting human rights and there is no evidence that shows the effectiveness of the application of the death penalty. Then, for drug dealers and producers, the death penalty is ineffective because it only increases awareness of the risks without actually providing a deterrent effect. Therefore, the government needs to evaluate the death penalty policy in Indonesia so that the credibility of the death penalty as a means of deterrence for serious criminals increases and creates a deterrent effect.